The phenomenon of viralization: the case of women's fashion in Brazil - Migliato, Caline Gonçalves; Pinsky, Vanessa Cuzziol; Aldea, Patricia González (Revista de Administração da UFSM, 2022)
Purpose – One of the biggest business challenges is to understand the phenomenon of viralization, which happens when certain products spread quickly among social strata are adopted by a majority and lose strength shortly afterwards. The importance of this study relies on the rapid economic impact of marketing viralization in women’s fashion. The main objective of this research is to understand how the main factors responsible for the viralization of fashion products are related. Design/methodology/approach – This is a qualitative and descriptive research, based on the sectorial case study method. Primary data were collected through in-depth interviews with market experts. Content analysis was performed using the three-level coding technique (open, axial, and theoretical), with the help of Atlas.TI software. Findings – The main results of the research indicate that viralization occurs when the following factors are related: functional and emotional attributes of the product, diffusers, communication, brand strategy, and consumer behavior. In the case of women's fashion, forecasting trends is important for the development of collections. It represents the company's way of being ahead of the consumer and producing the parts to meet their needs. Research limitations/implications – One research limit is related to the sample. Although they were specialists in the fashion sector, due to lack of time and resources, consumer groups were not included in the research. Originality/value – The main academic contribution of the study is the proposition of a theoretical model that explains the phenomenon of viralization in the sectoral case studied.